2012
DOI: 10.1007/s00428-012-1312-1
|View full text |Cite
|
Sign up to set email alerts
|

Flat epithelial atypia with and without atypical ductal hyperplasia: to re-excise or not. Results of a 5-year prospective study

Abstract: Flat epithelial atypia (FEA) of the breast have a tendency to calcify and, as such, are becoming increasingly detected by mammography. There is no consensus yet on whether to excise these lesions or not after diagnosis on core needle biopsies (CNB). We reviewed 3,948 cases of breast CNB between June 2004 and June 2009 correlating histomorphologic, radiological, and clinical features. There were 3.7 % (145/3,948) pure FEA and 1.5 % (58/3,948) concomitant FEA and atypical ductal hyperplasia (ADH). In the pure FE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
21
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(27 citation statements)
references
References 29 publications
4
21
2
Order By: Relevance
“…Although outside the scope of the current investigation, other retrospective studies have reported that cancer is found in approximately 3% to 13% of women with FEA on core needle biopsy who subsequently undergo surgical excision. 13,[30][31][32][33][34][35][36] This finding is not surprising, given the association between FEA and AH that we observed, and the known risk of an upgrade to cancer with surgical excision of AH. In addition to a small risk of detecting cancer at the time of surgical excision, multiple studies have reported finding other high-risk lesions (AH or lobular carcinoma in situ) in 20% to 52% of women undergoing excision of FEA found at core needle biopsy.…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…Although outside the scope of the current investigation, other retrospective studies have reported that cancer is found in approximately 3% to 13% of women with FEA on core needle biopsy who subsequently undergo surgical excision. 13,[30][31][32][33][34][35][36] This finding is not surprising, given the association between FEA and AH that we observed, and the known risk of an upgrade to cancer with surgical excision of AH. In addition to a small risk of detecting cancer at the time of surgical excision, multiple studies have reported finding other high-risk lesions (AH or lobular carcinoma in situ) in 20% to 52% of women undergoing excision of FEA found at core needle biopsy.…”
Section: Discussionsupporting
confidence: 67%
“…An issue in the current clinical management of FEA is the question of surgical excision when FEA is diagnosed with core needle biopsy. Although outside the scope of the current investigation, other retrospective studies have reported that cancer is found in approximately 3% to 13% of women with FEA on core needle biopsy who subsequently undergo surgical excision . This finding is not surprising, given the association between FEA and AH that we observed, and the known risk of an upgrade to cancer with surgical excision of AH.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…As reported in our systematic review, CCL-A diagnosed in core needle biopsies showed the presence of cancer in 9.4% of the subsequent excisions. 14 In more recent publications the underestimation risks ranged between 3.2% and 19%, [15][16][17][18][19][20][21][22][23][24] dependent upon study method differences, as some of the studies did not take into account radiological findings and radiological-pathological discordances. In larger vacuum biopsies more material is investigated, often showing lower underestimation risks [sometimes with no (in-situ) cancer] in subsequent excision biopsies.…”
Section: Introductionmentioning
confidence: 99%
“…Flat epithelial atypia (FEA), a commonly encountered lesion in stereotactic biopsies performed for grouped calcifications, has an uncertain risk level and is another histopathologic lesion where the management is variable in different practices (31). …”
Section: Histopathologic Considerationsmentioning
confidence: 99%